U. Eco, [et al.]. La nueva edad media, Madrid, Alianza Editorial, 1973. 321 p. - Hodara B., Joseph (El Colegio de México A.C., 1975)
U. ECO, F. COLOMBO, F. ALBERONI, G. SACCO, La nueva edad media, Madrid, Alianza Editorial, 1973.